Cyanide Content of Cassava Food Products Available in Australia - Quinn, Alicia A.; Myrans, Harry; Gleadow, Roslyn M. (Foods, 2022)
In 2009, Food Standards Australia New Zealand set a total cyanide content limit of 10 ppm for ready-to-eat cassava products to address food safety concerns about cyanogenic glucosides in cassava. This study surveys a range of cassava food products available in Melbourne, Australia, ten years after the implementation of these regulations. Of all the products tested, the mean cyanide content was greatest in ready-to-eat cassava chips (48.4 ppm), although imported ready-to-eat products had a higher mean cyanide content (95.9 ppm) than those manufactured in Australia (1.0 ppm). Cyanide was detected in frozen cassava products (grated mean = 12.9 ppm; whole root mean = 19.8 ppm), but was significantly reduced through processing according to packet instructions in both product types. Three methods were used to quantify total cyanide content: the evolved cyanide method, the picrate absorbance method and the picrate chart method, with satisfactory agreement between methods. The picrate absorbance and chart methods reported mean cyanide contents 13.7 ppm and 23.1 ppm higher, respectively, than the evolved cyanide method. Our results reaffirm the need for the ongoing testing of cassava food products, especially ready-to-eat products whose cyanide content will not be reduced before consumption.